NON-THERMAL INACTIVATION OF POLYPHENOLOXIDASE FROM JERUSALEM ARTICHOKE (HELIANTHUS TUBERUSUS L.) - Nyarko, G.; Afoakwah, N. A.; Dong, Y. (UDS International Journal of Development, 2019)
Polyphenoloxidase (PPO) is an enzyme that causes brown-colour in fruits and vegetables, and has been the object for the development of anti-enzymatic browning agents for food industries. In this study, PPO was extracted using the method as described by ÖNez, Karaku, & Pekyardimci, (2008) at 4 °C from Jerusalem artichoke (Helianthus Tuberusus L.). The PPO was inactivated using microwave and pulse magnetic field techniques. The kinetics of the non-thermal inactivation process was effectively modelled using Bigelow, Weibull and Hülsheger models. Results of this study revealed that, an increase in Tesla enhanced the inactivation of the PPO. Thus, treatment at 4.0-Tesla with 45-pulses were found to reduce the residual-activity of the enzyme to 32.6%. Also, the lowest PPO residual activity (≤ 30 %) occurred at high power (180 W – 300 W) for 15, 20, 25 and 30 min. when microwave was employed. With regards to the kinetic models, Hülsheger fitted the research data with an R2 ≥ 0.980. The application of pulse magnetic field and microwave was able to inactivate PPO from Helianthus tuberusus L., and may have a huge potential in the food industry for the control of enzymatic browning, which occurs during fruit and vegetable processing. Keywords: Non-thermal inactivation, Polyphenoloxidase, Pulse magnetic field, Jerusalem artichoke